Evaluation of Selected Nigerian Sorghum Malt Extract Quality as an Alternative to Barley in Beer Industries - Orji-Udezuka , A. C.; Chukwurah, E. N.; Ezemba , C. C. (African Journal of Education,Science and Technology (AJEST), 2020)
Barley malt which is the major raw material for beer production is usually imported from Europe or America with its very high import value by the Nigeria Government. It is therefore imperative that grains of similar agronomical values to barley are developed in Nigeria in order to sustain the brewing industry and this lead to research on Sorghum. The major reasons for this research were to evaluate selected Nigerian Sorghum Malt Extract quality for their chemical composition for beer production. The selected samples were obtained from Research Institute Ahmadu Bello University, Zaria, Nigeria and analyzed according to Standard methods of the Association of Official Analytical Chemist in the school laboratory. The proximate analytical results for the raw grains reviewed protein from 9.31-10.90 %, carbohydrate from 74.48-76.78 %, Moisture content from 9.03-9.16 %, crude fiber from 1.13-1.37 %, crude fat from 2.68-3.33 % and ash content from 0.85-0.92 %. Steeping and sprouting/germination at different temperature (15-18oC, 25-28oCand 37oC) (17h and 39h) were observed to be optimal at temperature 25-28oC for the varieties. Preliminary investigation depicted the presence of microorganisms which were inhibited using 0.1% formaldehyde. Proximate result on the malted grains reviewed protein ranged from 1.28-1.65 %, carbohydrate 85.21-89.88 %, Moisture content 6.44-10.94 %, crude fiber 12.70-20.40 %, crude fat from 0.90-1.40 % and ash content ranged from1.10-1.50 %. Results were presented using tables, ANOVA, post hoc test and chart and it showed that CSR-10 and CSR-02 exhibited good quality malt but CSR-02 had better quality malt than CSR-01.